Evaluasi Praktik Ekowisata di Kampung Tradisional Bena, Desa Tiwuriwu, Kabupaten Ngada, Nusa Tenggara Timur - Bata, Balduinus Bonaventura; Suryawan, Ida Bagus (JURNAL DESTINASI PARIWISATA; Vol 10 No 1 (2022): VOL 10, NO 1 (2022): (JANUARY - JUNE) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2022.v10.i01.p01, 2022)
Bena traditional village is a tourist village located in Tiwuriwu Village, Ngada Regency, NTT Province. This tourist village develops ecotourism as the basis for its tourism products. Ecotourism practices in Bena Village that have been running have a significant impact on environmental sustainability, utilizing socio-cultural economics for the local community. This study aims to evaluate the feasibility of ecotourism practices in Bena village by using ecotourism principles as a parameter to determine the feasibility of ecotourism. Qualitative method is used as a tool to analyze this research with a qualitative descriptive approach. The data were searched by using interview, documentation and observation methods. The results showed that several ecotourism practices in Bena village were in accordance with the principles of ecotourism. Practices that do not meet the principles of ecotourism require a strategic model that is able to meet these deficiencies. Keywords : Ecotourism, Principle, Practice